2009
DOI: 10.1007/s11205-009-9473-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Analysis of the Orientations to Happiness Questionnaire in Taiwanese Undergraduate Students

Abstract: Know thyself, Flow, Hedonism, Eudaimonism, Positive psychology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It is notable that this research has since been replicated with a variety of populations (e.g. students, teachers, the elderly) in over 27 nations, with results confirming the strong relationship between the full life and life satisfaction (Chan, 2009;Chen, Tsai, & Chen, 2010;Park et al, 2009;Ruch, Harzer, Proyer, Park, & Peterson, 2010;Vella-Brodrick, Park, & Peterson, 2009).…”
Section: Pathways To Wellbeingmentioning
confidence: 56%
“…It is notable that this research has since been replicated with a variety of populations (e.g. students, teachers, the elderly) in over 27 nations, with results confirming the strong relationship between the full life and life satisfaction (Chan, 2009;Chen, Tsai, & Chen, 2010;Park et al, 2009;Ruch, Harzer, Proyer, Park, & Peterson, 2010;Vella-Brodrick, Park, & Peterson, 2009).…”
Section: Pathways To Wellbeingmentioning
confidence: 56%
“…The SWLSTaiwan version has been demonstrated to have strong internal reliability (r = 0.84) (Chen and Kee 2008) and its gender (Wu and Yao 2006) as well as time invariance (Wu et al 2009b) had been reported. Also, the SWLS-Taiwan version has been shown to correlate with appropriate criterion measures (see Chen et al 2010;Wu and Yao 2008). This scale employed a seven-point Likert scale ranging from strongly disagree (1) to strongly agree (7).…”
Section: Satisfaction With Life Scalementioning
confidence: 99%
“…Psychologists have proposed several pathways to reduce this discrepancy, including socalled ''flow experiences'' (Chen et al 2010;Csikszentmihalyi 1990;Peterson et al 2005), which occur when skill and challenge are balanced. However, the mechanisms underlying the relationship between flow experiences and life satisfaction have rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Peterson and colleagues found that the endorsement of each of these orientations is positively related to satisfaction with life. Numerous studies have replicated the relations between these orientations and different indicators of subjective well-being, also across different countries (e.g., Buschor et al 2013;Chan 2009;Chen et al 2010;Peterson et al 2007;Proyer et al 2013;Ruch et al 2010;Vella-Brodrick et al 2009). …”
Section: Introductionmentioning
confidence: 96%